#TITLE_ALTERNATIVE# - SETIAWAN (NIM : 11414027), HELMI
Black soybean is a legume crop that is less attractive to the public due to the lack of processed products. The production of black soybean sprouts from black soybeans will be able to be a solution to the diversity of food for the people in Indonesia. The quality of black soybean sprouts can be affected by the presence of light. Blue light which is one spectrum of light that appears to have a role in influencing the quality of sprouts. This study aims to determine the effect of blue light irradiation time during control (without light), 4 hours, 8 hours, 12 hours, 16 hours, 20 hours, and 24 hours on morphology, biomass, chlorophyll levels, and isoflavone levels (deidzein, glycitein , and genistein) Black soybean sprouts (Glycine max L. Merr.) Detam-1 variety. This research was conducted on March 6 to April 20, 2018 at Labtek 1A in a dark room in a biomass production system laboratory. The research process starts from making Germination Chamber which functions to germinate seeds in a space that is isolated from the surrounding environment. Germination starts from seed selection, then the seeds are soaked for 6 hours in a fungicide solution. The seeds are rinsed with water, then added to the Germination Chamber for 4 days. During 4 days the seeds are watered using sprayed water using spray every 4 hours. Observations were made on day 2 and day 4 for morphology and biomass, while measurements of germination, chlorophyll and isoflavones were only carried out on day 4. Morphological observations were carried out by taking hypocotyl and root length data, while biomass measured wet weight, dry weight, and moisture content. Biomass and morphology observation data were tested with One Way ANOVA statistic with α = 0.05 or 5% error rate which was then carried out by Duncan or DMRT (Duncan Multiple Range Test) follow-up to see the significance of each treatment, while chlorophyll and isoflavone levels were tested descriptively. The results showed that the control treatment, 4 hours, 8 hours, 12 hours, 16 hours, 20 hours, and 24 hours had no significant effect on the hypocotyl length of the second day, hypocotyl length on day 4, root length on day 2, weight wet day 2, dry day 2, dry weight day 4, day 2 water level, and germination power. While a significant difference occurred at the root length of day 2, water content on day 4, and wet weight on day 4. Treatment of irradiation for 8 hours and 12 hours had a significant effect on inhibiting the root length of day 4. In the treatment 8 hours, 12 hours, and 16 hours had significant effect in reducing the water content and wet weight of the sprouts on the day 4. The results of chlorophyll and isoflavone levels (daidzein, glycitein, and genistein) showed fluctuating values, where the highest chlorophyll value in the 8-hour treatment was 0.124 mg / L, while the highest isoflavone level was at 24-hour treatment of 0.600 ppm and 0.619 ppm for the womb. daidzein and genistein, as well as a 16-hour treatment of 0.594 ppm for glycitein content.